PEMBELAJARAN KALKULUS BERBASIS 4K UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Siti Napfiah; Yunis Sulistyorini (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
This article describes the application of 4C (Critical, Creative, Communicative, and Collaborative) in Calculus learning to improve students' ability to solve mathematical problems. This research was classroom action research. Subjects of this study were students of IKIP Budi Utomo Malang Mathematics Education program. Steps of 4C learning that can improve problem solving skills were (1) students were given problems that encourage critical and creative thinking, (2) they were asked to collaborate and communicate in groups, (3) demonstration activities that require each student to communicate in front of classmates, (4) students asked to make problems that encourage creative thinking. The results of the study indicate that there was an increase in student’s ability to solve problems after being given 4C learning. In the preliminary study, most students were able to understand problem, but few students were able to make plan and implement plan. The average score of students’ problem solving skill improved from 22.5 in the preliminary study to 60 in the first cycle and 79.75 in the second cycle. So 4C learning can improve students’ problem solving skills.